TCAD: Vocabulary acquisition tool for motivating bilingual pupils with hearing impairment in learning English - Santichai Wicha (2018)
© Springer Science+Business Media New York 2013. This chapter describes a software system, Total Communication Animated Dictionary (TCAD), developed to support the acquisition and retention of English vocabulary of pupils with hearing impairment in their bilingual education program. TCAD employs a variety of visual aids and animated features (e.g. lip reading, finger spelling, sign and animation) to optimise their vocabulary acquisition. To enhance their retention TCAD includes stories and games which are based on the learnt vocabulary and set within the local context and culture of primary school pupils. TCAD is tested with a set of primary pupils with hearing-impaired from a school based in Chiang Mai, Thailand. The initial investigation showed promising results in the acquisition and retention of English vocabulary. Teachers have noted an improved motivation and enthusiasm among their pupils in learning English as TCAD has provided a forum for social interaction and communication among the pupils.